Development of the noise questionnaire in the online learning process and implications for counseling - Ardimen Ardimen; Rafsel Tas'adi; Murisal Murisal; Gusril Kenedi; Hardivizon Hardivizon; Romi Fajar Tanjung (Institute of Advanced Engineering and Science, 2024)
Starting with online learning requires a lot of attention such as focus, comfortable sitting, and avoiding distractions such as noise. A noise questionnaire instrument is an evaluation tool designed to identify the experience of students in the online learning process. This instrument was developed based on a literature review on noise and online learning. The instrument first stage was given to 110 students and the instrument second stage was given to 460 students in seven universities in Indonesia, 99 male and 361 female respondents aged 18-30 years. The instrument was designed based on DeVito’s noise theory: physical noise, physiological noise, psychological noise, and semantic noise. The statistical test of the instrument used confirmatory factor analysis (CFA) to find the goodness of fit index model. The results of the noise instrument factor analysis show a fit model, acceptable validity, and high internal consistency (α=0.86). The findings of this study produce valid and reliable instruments for identifying noise indicators that are dominant in online learning activities. The results of identifying noise in online learning can be used to design guidance and counseling programs or plan actions to deal with noise in online learning according to the data obtained.